Clostridium ramosum Osteomyelitis in an Immunocompetent Patient After Traumatic Injury. Issue 2 (March 2015) - Dahya, Vishal; Ramgopal, Moti; Collin, Berjan; Robinson, Marjorie
Abstract : Abstract: Clostridium ramosum is an anaerobic, spore-forming, gram-positive bacterium that is found commonly in the intestinal flora and is very rarely implicated as being pathogenic. It is a member of the genus Clostridium and is generally considered as being less virulent as other members of the Clostridium species such as C perfringens, C difficile, or C tetani . We present the first case reported of osteomyelitis caused by C ramosum in an immunocompetent patient after traumatic injury with failure to respond to antimicrobial treatment.